2009
DOI: 10.1007/s00586-009-1045-2
|View full text |Cite
|
Sign up to set email alerts
|

Value of MRI imaging prior to a kyphoplasty for osteoporotic insufficiency fractures

Abstract: Previous studies have shown the safety and effectiveness of balloon kyphoplasty in the treatment of osteoporotic vertebral compression fractures (OVCFs). MRI and particularly the short tau inversion recovery (STIR) sequence are very sensitive for detecting vertebral edema as a result of fresh fractures or micro-fractures. Therefore, it has a great therapeutic relevance in differentiating vertebral deformities seen by conventional X-ray and CT scans. Although an MRI scan is expensive, to my knowledge no study h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 15 publications
2
29
0
3
Order By: Relevance
“…The STIR sequence is very sensitive for the detection of osseous and soft-tissue edema as a result of fractures or microfractures 28 and is routinely used to identify such edema in the cervical spine and other skeletal sites. 15 One study showed STIR to be superior to CT in detecting subtle fractures, such as insufficiency fractures.…”
Section: Discussionmentioning
confidence: 99%
“…The STIR sequence is very sensitive for the detection of osseous and soft-tissue edema as a result of fractures or microfractures 28 and is routinely used to identify such edema in the cervical spine and other skeletal sites. 15 One study showed STIR to be superior to CT in detecting subtle fractures, such as insufficiency fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the presence of a BME may be an essential predictor for a successful pain relief and correction of deformity after treatment of painful vertebral fractures by kyphoplasty. As a consequence, several authors included only patients with vertebral BME revealed by MRI in their trials [1,4,[10][11][12][13][14] and observed pain relief after kyphoplasty. To our knowledge, a comparative evaluation of the short and long-term outcomes of kyphoplasty in painful osteoporotic vertebral fractures with and without MRI edema has not been reported previously.…”
Section: Introductionmentioning
confidence: 99%
“…The paper by Spiegl et al [23] published in the September issue reports the conclusions of a study aiming at identifying the best imaging prior to kyphoplasty. As MRI, especially the STIR sequence, is very sensitive in detecting vertebral edema resulting from fresh fractures, the authors hypothesized that MRI should be superior to X-ray and CT scan in accurately pinpointing the vertebral bodies to be treated and in distinguishing fresh fractures or microfractures from old fractures.…”
Section: Osteoporotic Vertebral Fractures: Value Of Mri Prior To Kyphmentioning
confidence: 99%